The role of neo-adjuvant therapy in cholangiocarcinoma: A systematic review - Cremen, Sinead; Kelly, Michael E.; Gallagher, Tom K. (Frontiers in Oncology, 2022)
Introduction: Cholangiocarcinoma (CCA) is the most common malignancy affecting the biliary tree. The only curative treatment is surgical resection, aiming for negative margins (R0). For those who have locally advanced disease, which is borderline resectable, neoadjuvant chemoradiation presents an opportunity to reduce tumour size and allow for surgical resection. The aim of this review is to establish the role of neoadjuvant therapy in each subtype of CCA and establish its impact on survival. Methods: Search terms such as ‘neoadjuvant therapy’ and ‘cholangiocarcinoma’ were searched on multiple databases, including Pubmed, Ovid and Embase. They were then reviewed separately by two reviewers for inclusion criteria. 978 studies were initially identified from the search strategy, with 21 being included in this review. Results: 5,009 patients were included across 21 studies. 1,173 underwent neoadjuvant therapy, 3,818 had surgical resection alone. 359 patients received Gemcitabine based regimes, making it the most commonly utilised regimen for patients CCA and Biliary Tract Cancer (BTC). Data on tolerability of regimes was limited. All included papers were found to have low risk of bias when assessed using The Newcastle Ottawa Scale. Patients who underwent neoadjuvant therapy had a similar median overall survival compared to those who underwent upfront surgery (38.4 versus 35.1 months respectively). Pre-operative CA19-9, microvascular invasion, perineurial invasion and positive lymph nodes were of prognostic significance across BTC and CCA subtypes. Conclusion: Neoadjuvant therapy and surgical resection is associated with improved patient outcomes and longer median overall survival compared to therapy and upfront surgery, however heterogeneity between research papers limited the ability to further analyse the significance of these results. Although initial studies are promising, further research is required in order to define suitable treatment protocols and tolerability of neoadjuvant regimes.